Microtopographic reconstruction improves soil erosion resistance and vegetation characteristics on the slopes of large dump sites in semi-arid areas - Tian, Xiumin; Yin, Ruiping; Wang, Jian; Dong, Lei; Cheng, Bo; Liu, Hu; Ge, Nan (Frontiers in Environmental Science, 2022)
In view of the management of slopes in large mine dumps in semi-arid regions, this study explored different methods for controlling soil erosion and improving the microenvironment of the surface of such slopes. Focusing on microtopography modifications and vegetation measures on the slopes of a large mine dump in a semi-arid region, the soil erosion resistance of the slope was continuously monitored using installed observation plots. In addition, the characteristics of plant communities that thrived on the dump were investigated. The results indicate that the soil erosion resistance, soil organic matter content, and biodiversity increased to different degrees in the large mine dump that experienced microtopography modifications and implemented vegetation measures compared with those of slopes managed only by soil cover and planting. Compared with that in the control plot, under the same vegetation restoration measures, the macroaggregate content in the four plots that implemented microtopography modifications increased by 20%, 24%, 21%, and 30%; the soil erodibility (K-factor) decreased by 7.8%, 8.5%, 10%, and 10.7%; and the soil organic matter increased by 2%, 4.5%, 3.4%, and 4.7%. Microtopography modification consisting of U-shaped blocking boards and fixed rods embedded in the slope, combined with vegetation measures, resulted in a protective effect, which in turn induced the highest diversity, evenness, and richness index values of 2.35, 0.87, and 1.94, respectively. The study results revealed that a combination of microtopography modifications and vegetation measures can be used to achieve effective vegetation restoration, prevent soil erosion, and create different microhabitats, indicating that our approach is an effective way to control critical issues affecting large mine dumps in semi-arid regions.